(untitled) (International Journal of Innovative Technologies in Economy, 2018)
The purpose of the study was to analyze the economic effects of international labour migration and its impact on the economic development of Ukraine. The positive effects for Ukraine are the growth of household incomes, the increase in foreign currency, the reduction of unemployment and state unemployment payments. The negative factors are the brain drain, the loss of the most dynamic part of the country’s labor potential, the worsening of the demographic situation, and the increase in the burden on the pension fund.